Phylogeographic data revealed shallow genetic structure in the kelp Saccharina japonica (Laminariales, Phaeophyta). (December 2015) - Zhang, Jie; Yao, Jian-Ting; Sun, Zhong-Min; Fu, Gang; Galanin, Dmitry; Nagasato, Chikako; Motomura, Taizo; Hu, Zi-Min; Duan, De-Lin
Abstract Background Population structure and genetic diversity of marine organisms in the Northwestern Pacific Ocean exhibited complex patterns.Saccharina japonica is a commercially and ecologically important kelp species widely distributed along the coast of Japan Sea. However, it is still poorly known about population genetics and phylogeographic patterns of wildS. japonica populations on a large geographic scale, which is an important contribution to breeding and conservation of this marine crop. Results We collected 612 mitochondrialCOI andtrn W-trn L sequences. Diversity indices suggested thatS. japonica populations along the coast of Hokkaido exhibited the highest genetic diversity. Bayesian Analysis of Population Structure (BAPS) revealed four clusters in the kelp species (cluster 1: Hokkaido and South Korea; cluster 2: northwestern Hokkaido; cluster 3: Far Eastern Russia; cluster 4: China). The network inferred from concatenated data exhibited two shallow genealogies corresponding to two BAPS groups (cluster 2 and cluster 3). We did not detect gene flow between the two shallow genealogies, but populations within genealogy have asymmetric gene exchange. Bayesian skyline plots and neutrality tests suggested thatS. japonica experienced postglacial expansion around 10.45 ka. Conclusions The coast of Hokkaido might be the origin and diversification center ofS. japonica . Gene exchange amongS. japonica populations could be caused by anthropogenic interference and oceanographic regimes. Postglacial expansions and gene exchange apparently led to more shared haplotypes and less differentiation that in turn led to the present shallow phylogeographical patterns inS. japonica .